Range pole with integrated power system - HANKINS; CHRISTOPHER; MONSEF; ERIC (2000)
A range pole and in-line detachable battery module assembly including a range pole (10) with an elongated tubular range pole shell (102) which has a female cap assembly (108) and a male cap assembly (26) at opposite ends. A detachable battery module (12) includes a tubular battery-module shell (24) which has a male cap (26) at one end that is adapted to mate with female cap assembly 108. A detachable tip (14) includes a ribbed aluminum tip body (150) having external ribs (152) formed in the sides thereof and a stainless steel tip (160). The male cap assembly (26) at the other end of the range pole (10) is to be used for connection to other equipment. In the present embodiment, the male cap assembly (26) at the top end of the range pole is coupled to a GPS antenna/receiver (16).